The International Council for Coach Excellence
The International Council for Coach Excellence (ICCE) is a not-for-profit, international organization with the mission of promoting coaching as an internationally accepted profession. ICCE members seek to enhance the quality of coaching at every level of sport. Every day around the world, tens of millions of athletes run, jump, throw, catch, swim and participate in other sport activities. And every day around the world, millions of coaches help those athletes chase their dreams. The ICCE believes that international collaboration and exchange can accelerate positive change in the realm of coaching development and help these coaches give athletes around the world a chance to pursue excellence. By joining together in the ICCE, members seek to develop an international framework to share this vision with every nation in the world`s sporting community. The target audiences for the ICCE are National Representative Bodies responsible for coach education; institutions that deliver coach education; individuals who design and deliver coach education; coaches; and the international sport community at large. The expected outcomes of the ICCE initiative are: A network of international organizations responsible for the development of coaches in their respective nations. International accords on coaching issues such as ethics, safety, and knowledge/competency. An international coaching culture that supports the values of Olympism: integrity, honesty, fairness, inclusion, tolerance, and commitment to excellence. The ICCE is uniquely qualified to address its mission because its members comprise the world`s leaders in coaching development. There exists no other international sports body that focuses on programs for the individuals who introduce, teach, and deliver sport daily-coaches.